SYSTEMATIC LITERATURE REVIEW OF FORENSIC SCIENCE AND AL-QARINAHIN PROMINENT SHARIAH LITERATURE (International Seminar on Syariah and Law (INSLA), 2021)
Islamic law truly recognizes and appreciates the existence of science. This article explored the existence of forensic science elements in prominent shariah literature. The elements were existed to be integrated with the principles of evidence in Islam. Based on the reviews, prominent scholars views in al-qarīnahcan best be organised under the three themes namely; the admissibility of al-qarīnahon civil, ta‘zīr, and ḥudūdcases. In fact, that there are several literatures found to highlight the forensic science elements, but the discussion was very limited and unorganised. It is evident that the assimilation between science and Islam existed through the integration of forensic science and al-qarinah. These findings can become the foundation of further theory of forensic science admissibility in Islamic law. This study suggests more research to be conducted within a wider scope to explore more in this field.